Geochemical and mineralogical aspects of sulfide mine tailings. (June 2015) - Lindsay, Matthew B.J.; Moncur, Michael C.; Bain, Jeffrey G.; Jambor, John L.; Ptacek, Carol J.; Blowes, David W.
Highlights: Geochemistry and mineralogy of sulfide mine tailings are reviewed. Case studies highlight metal(loid) release, transport and attenuation processes. Interactions among chemical, biological and physical processes are complex. Effective tailings management requires comprehensive understanding of processes. Abstract: Tailings generated during processing of sulfide ores represent a substantial risk to water resources. The oxidation of sulfide minerals within tailings deposits can generate low-quality water containing elevated concentrations of SO4, Fe, and associated metal(loid)s. Acid generated during the oxidation of pyrite [FeS2 ], pyrrhotite [Fe(1− x ) S] and other sulfide minerals is neutralized to varying degrees by the dissolution of carbonate, (oxy)hydroxide, and silicate minerals. The extent of acid neutralization and, therefore, pore-water pH is a principal control on the mobility of sulfide-oxidation products within tailings deposits. Metals including Fe(III), Cu, Zn, and Ni often occur at high concentrations and exhibit greater mobility at low pH characteristic of acid mine drainage (AMD). In contrast, (hydr)oxyanion-forming elements including As, Sb, Se, and Mo commonly exhibit greater mobility at circumneutral pH associated with neutral mine drainage (NMD). These differences in mobility largely result from the pH-dependence of mineral precipitation–dissolution and sorption–desorption reactions. Cemented layers of secondary (oxy)hydroxide and (hydroxy)sulfate minerals, referred to as hardpans, may promote attenuation of sulfide-mineral oxidation products within and below the oxidation zone. Hardpans may also limit oxygen ingress and pore-water migration within sulfide tailings deposits. Reduction–oxidation (redox) processes are another important control on metal(loid) mobility within sulfide tailings deposits. Reductive dissolution or transformation of secondary (oxy)hydroxide phases can enhance Fe, Mn, and As mobility within sulfide tailings. Production of H2 S via microbial sulfate reduction may promote attenuation of sulfide-oxidation products, including Fe, Zn, Ni, and Tl, via metal-sulfide precipitation. Understanding the dynamics of these interrelated geochemical and mineralogical processes is critical for anticipating and managing water quality associated with sulfide mine tailings.